If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5s + -11 = 13 + s Reorder the terms: -11 + 5s = 13 + s Solving -11 + 5s = 13 + s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-1s' to each side of the equation. -11 + 5s + -1s = 13 + s + -1s Combine like terms: 5s + -1s = 4s -11 + 4s = 13 + s + -1s Combine like terms: s + -1s = 0 -11 + 4s = 13 + 0 -11 + 4s = 13 Add '11' to each side of the equation. -11 + 11 + 4s = 13 + 11 Combine like terms: -11 + 11 = 0 0 + 4s = 13 + 11 4s = 13 + 11 Combine like terms: 13 + 11 = 24 4s = 24 Divide each side by '4'. s = 6 Simplifying s = 6
| f(x+7)=x^2+8x+5 | | -7-7x=-16 | | 12x+6=x | | 5v-2=2+2v-2+1 | | -18=-2+2w | | 6n-7=n+3 | | 2m+11=33 | | .40x+0.06(30)=9.8 | | -8+x+3x=-8+4x | | 14x=2x^2-16 | | 7=3+16q | | -4=3x-5(x+1) | | G(-x)=3x^2-3x+5 | | S^6-t^6=(s^2)3-(t^2)3 | | 35x+y=1230 | | 2x+3y+z=22 | | 6x+14=-42-2x | | 2(6y-5)=20 | | 2(x+4)-x=11 | | N-64=312 | | 0.222x+0.6667x=7 | | -15+5m=7m-5m | | x+1=4x+6-3x | | (4x+2)-x=11 | | 1=8n-9 | | 5(4m+1)=20 | | 2x+7-8x=13-15x+9x-6 | | x+0.09x=721 | | 279+0.38= | | 0=3(2x-8) | | 279=64-w | | 7-x=4-9x |